An appreciative enquiry of family health support - O'Neill, Debra (My University, 2024)
The evidence suggests that women are less likely to engage in problematic substance use than their male counterparts, but we have also seen the prevalence of drug use, among women aged 15– 34 years, double between 2002/03 and 2019/20 from 4.2% to 8.4%. This could be the result of the significant increase in the use of cocaine among women aged 15-24 years, up from 1.10% in 2002/2003 to 4.5% in 2019/2020. Across Europe women now make up about 20% of all new patients in specialised drug treatment programs and about 25% of all individuals with major problematic substance use. For many, being a woman with problematic substance use provides a double stigma, being a pregnant woman or a mother, creates very complex challenges.
PUBLISHED
An exploration of a pilot programme to holistically support pregnant women who use substances, establishing a comprehensive wrap around service in Dublin's Finglas and Cabra area
Keywords: Inclusive Society; Addiction and substance abuse; Maternity Care; PARENTS; Pregnancy; WOMEN'S HEALTH